Hubungan Paritas, Usia Dan Pendidikan Ibu Hamil Trimester III Dengan Tingkat Kecemasan Dalam Menghadapimasa Menjelang Persalinan Di Puskesmas Petir - Fitri Yanti, Fani; Hasrida (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: to identify Anxiety in third trimester pregnant women is caused by fear of facing childbirth which is caused by several factors, including parity, age and education. To determine the relationship between parity, age and education of pregnant women in the third trimester with the level of anxiety in facing the period leading up to childbirth at the Petir Health Center, Serang Regency in 2023. Methods: This article is quantitative analytical with a cross sectional design. The sample in this study was 55 respondents from third trimester pregnant women using a total sampling technique. The research instrument used a questionnaire. Primary data was analyzed using the square test. Results: The results of univariate analysis showed that the majority of third trimester pregnant women had low risk parity 65.5%, low risk age 67.3%, low education 63.6%, and moderate anxiety level 60.0%. The results of the bivariate analysis showed that there was a significant relationship between parity (p value = 0.018), age (p value = 0.006) and education (p value = 0.002) with the anxiety level of pregnant women in the third trimester in facing the period approaching delivery. Conclusion: parity, age and education are related to the level of anxiety of pregnant women in the third trimester in facing the period approaching delivery. Pregnant women are expected to be able to take advantage of health services to reduce anxiety before giving birth, so that during labor the mother will be calmer